Role of nutrition in providing pro-/anti-inflammatory balance : emerging research and opportunities - Günşen, Uğur, 1965-; Atan, Ramazan Mert, 1995- (Hershey, PA : Medical Information Science Reference, 2020)
"This book explores the role of nutrition in providing pro-/anti-inflammatory balance. It also examines the formation process of inflammation, biomarkers used for diagnosis, and diseases affected by inflammation"--
The Process of Acute and Chronic Inflammation, Biomarkers and Their Relationship with Diseases / Sedat Demir, HC Clinic, Turkey -- Epidemiology of Inflammation Related Diseases / Kevser Tarı Selçuk, University of Bandırma Onyedi Eylül, Faculty of Health Science, Department of Nutrition and Dietetics, Turkey -- Macronutrients Having Properties Pro/Anti-Inflammatory / Uğur Günşen, University of Bandırma Onyedi Eylül, Faculty of Health Science, Department of Nutrition and Dietetics, Turkey, Ramazan Mert Atan, University of Bandırma Onyedi Eylül, Faculty of Health Science, Department of Nutrition and Dietetics, Turkey -- Inflammatory Effects of Micronutrients / Leyla Teyfikoğlu Pehlivan, University of Trakya, Faculty of Health Science, Department of Nutrition and Dietetics, Turkey -- Pro/Anti Inflammatory Bioactive Proteins and Peptides / Fatma Esra Güneş, University of Marmara, Faculty of Health Science, Department of Nutrition and Dietetics, Turkey -- Pro / Anti Inflammatory Food Supplements (Probiotics and Prebiotics) / Hüseyin Eseceli, University of Bandırma Onyedi Eylül, Faculty of Health Science, Department of Nutrition and Dietetics, Turkey -- Inflamation Dietary Inflammatory Index and the Role of Different Diet Types / Ramazan Mert Atan, University of Bandırma Onyedi Eylül, Faculty of Health Science, Department of Nutrition and Dietetics, Turkey, Uğur Günşen, University of Bandırma Onyedi Eylül, Faculty of Health Science, Department of Nutrition and Dietetics, Turkey.
Keywords: Inflammation; Dietary Supplements; Inflammation Mediators; Biomarkers; Immune System Phenomena; Nutritional Physiological Phenomena